Ultrathin diamond composite material and preparation method thereof
By using diamond micro powder, composite adhesive and cemented carbide matrix, combined with pulse current sintering technology, the extremely thin diamond composite material prepared solves the problems of low processing efficiency and easy wear in the existing technology, achieving high hardness, toughness and wear resistance, and extending the tool service life.
Patent Information
- Application Number
- CN202510188859.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-20
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-02-20
AI Technical Summary
The existing extremely thin polycrystalline diamond composite materials are inefficient and easy to wear during processing, and have high tool production costs, complex structure, insufficient impact resistance and short service life.
Diamond powder, composite adhesive and cemented carbide matrix are used, and the composite adhesive contains zirconia and polyimide. Extremely thin diamond composite materials are prepared by pulse current sintering technology.
It achieves a balance of hardness and toughness of the material, improves wear resistance and impact resistance, extends the tool service life, and improves processing accuracy and surface quality.
Abstract
Description
Technical Field
[0001] The present application relates to the field of diamond materials, and more specifically, to an ultra-thin diamond composite material and a preparation method thereof. Background Art
[0002] Polycrystalline diamond composite materials (also known as diamond composite sheets, English name: Polycrystalline Diamond, often referred to as PCD) are widely used in the production of superhard cutting tools. Compared with cutting tools made of traditional cemented carbide, tool steel, ceramics and other materials, cutting tools made of polycrystalline diamond composite materials have the advantages of high speed and high efficiency, energy saving and environmental protection, high processing accuracy, high processing surface finish, high wear resistance, high life, and high thermal conductivity. Polycrystalline diamond composite materials are made by sintering a polycrystalline diamond layer and a cemented carbide (WC-Co alloy) matrix at high temperature (about 1500℃) and high pressure (about 6GPa). The thickness of the polycrystalline diamond layer of the finished diamond composite sheet used to make superhard cutting tools generally does not exceed 1mm, usually 0.3mm-0.8mm.
[0003] With the expansion of the application of PCD tools in the field of processing, and the widespread use of difficult-to-process materials in the manufacturing industry (such as automobiles, aerospace, electronics, energy and other industries), especially for the high-speed, high-efficiency and high-precision processing needs of materials such as glass, ceramics, carbon fiber composites, high-temperature alloys, and high-viscosity metals, the working surface thickness of the workpiece to be processed is relatively large. The general thin polycrystalline diamond layer of PCD (polycrystalline diamond working layer is usually about 0.5mm, generally greater than 0.2mm, less than 3mm) is difficult to meet the processing needs. Repeated processing is required during processing, and the processing efficiency is low. During the repeated processing, there is a mismatch between the front and rear processing trajectories, and the processing accuracy is not up to standard, requiring subsequent fine processing. In addition, the wear problem is serious during the repeated processing, and the tool needs to be replaced frequently, which affects the processing efficiency and is not conducive to automatic batch operation of the assembly line. If the working layer of the tool can be spliced by welding or other methods to meet the processing needs, there are shortcomings such as complex structure and high tool manufacturing cost, high brittleness, insufficient impact resistance, easy cracking and delamination at the splicing (welding) joint, and low service life. Summary of the invention
[0004] In order to solve the problem that existing ultra-thin polycrystalline diamond composite materials need to be repeatedly processed, resulting in low efficiency and easy wear, the present application provides an ultra-thin diamond composite material and a preparation method thereof.
[0005] The present application provides an ultra-thin diamond composite material and a preparation method thereof using the following technical solutions: An ultra-thin diamond composite material and a preparation method thereof, comprising diamond micropowder, a composite binder and a cemented carbide matrix, wherein the composite binder comprises 60-80% of zirconium oxide and 20-40% of polyimide, and the amount of the composite binder is 8-12% of the mass of the diamond micropowder.
[0006] By adopting the above technical solution, diamond powder is used as the main hard component to provide high hardness and wear resistance. Zirconia and polyimide in the composite binder cooperate with each other. Zirconia provides hardness and stability, and polyimide provides flexibility and impact resistance. The combination of the two can effectively bond diamond powder and improve the comprehensive performance of the material. The cemented carbide matrix provides solid support for the entire composite material, withstands the cutting force during processing, and ensures the stability of the material during use. The amount of binder is between 8-12%, which helps to form a tight structure and improve the density of the material. This combination gives the material a good balance of hardness and toughness, and can effectively resist wear and impact during processing. When processing various materials, especially difficult-to-process materials, it can maintain the shape and performance of the tool, extend the service life of the tool, and at the same time obtain higher processing accuracy and surface quality.
[0007] Optionally, the preparation method of the composite binder is: Disperse zirconium oxide powder with a particle size of 40-60 nm in an organic solvent, add a surfactant, and stir to react for 2-4 hours; Under nitrogen protection, a mixed solution of diamine and dianhydride is added to the zirconium oxide dispersion, the molar ratio of diamine to dianhydride is maintained at 1:1, the reaction temperature is controlled at 150-200°C, and the reaction time is 4-8 h; After the reaction is completed, the reaction product is cooled, washed and dried to obtain a composite adhesive.
[0008] By adopting the above technical solution, the surfactant reacts with the functional groups on the surface of zirconium oxide to enhance its surface activity. Under nitrogen protection, diamine and dianhydride undergo polycondensation reaction on the surface of zirconium oxide to form polyimide and coat zirconium oxide. Nitrogen protection is to prevent side reactions such as oxidation during the reaction. In the composite binder prepared by this method, zirconium oxide is uniformly coated with polyimide, so that the binder has both the high hardness of zirconium oxide and the flexibility of polyimide, and can better bond diamond micropowder, improve the internal bonding strength of the material, and thus improve the overall performance of the material.
[0009] Optionally, particles with a particle size of 10-100 nm in the diamond micropowder account for 10-15% of the total mass of the diamond micropowder, and particles with a particle size of 1-10 μm in the diamond micropowder account for 85-90% of the total mass of the diamond micropowder.
[0010] By adopting the above technical solution, nano-diamond powder can fill the gaps between micron-sized diamond powders to form a denser microstructure. Nano-diamond powder has a high specific surface area and surface energy, which can enhance the bonding with the binder and improve the hardness and wear resistance of the material. Micron-sized diamond powder provides the main supporting skeleton to ensure the overall strength of the composite material. This particle size distribution optimizes the stacking mode of diamond powder, making the microstructure of the material more compact, and improving the hardness and wear resistance of the material. During the processing, the workpiece material can be cut more effectively, and the shedding of diamond powder can be reduced, which can extend the service life of the tool.
[0011] Optionally, yttrium micropowder with a particle size of 40-80 nm is also included, and the added amount of the yttrium micropowder is 0.2-0.4% of the mass of the diamond micropowder.
[0012] By adopting the above technical solution, during the sintering process, when the temperature of the material system rises and diamond begins to crystallize and grow, the surface energy and crystal structure of the rare earth element particles are somewhat different from those of diamond. This difference makes it easier for diamond atoms to gather on the surface of the rare earth element particles and begin to crystallize, thereby increasing the number of nucleation sites. In addition, the rare earth elements will hinder the diffusion and deposition of atoms on the surface of the grains, slowing down the growth rate of the grains. Under this dual effect, the diamond grains are refined to form a more uniform and fine grain structure.
[0013] Optionally, the cemented carbide substrate is a WC-TiC-Co cemented carbide substrate.
[0014] By adopting the above technical solution, a WC-TiC-Co cemented carbide matrix is selected, WC is used as a hard phase to provide hardness, TiC further improves hardness and wear resistance, and Co is used as a bonding phase to ensure the toughness of the cemented carbide. The composition combination of this cemented carbide matrix makes it have high hardness, high wear resistance and good toughness, can provide good support for composite materials, enhance the overall strength and stability of the tool, enable it to adapt to various complex processing environments, such as high-speed cutting, intermittent cutting, etc., and help to increase the service life of the tool.
[0015] In a second aspect, the present application provides a method for preparing an ultra-thin diamond composite material, using the following technical solution: A method for preparing an ultra-thin diamond composite material comprises the following steps: Mix the diamond powder with the composite binder, put the cemented carbide substrate into the mold, and then stack the diamond powder containing the composite binder on one side of the cemented carbide substrate with a stacking thickness of 2-3 mm; Pulse current is used to heat and sinter the mold, the pressure is set to 4-5GPa, and the sintering temperature is set to 700-900℃ to obtain an extremely thin diamond composite material.
[0016] By adopting the above technical solution, pulse current sintering can effectively avoid the graphitization transformation of diamond due to long-term heating at high temperature compared to traditional 1500℃ high temperature and high pressure sintering, and can refine the grains. During the pulse current sintering process, due to the extremely short heating time, the diamond powder completed the sintering process before reaching the critical condition of graphitization. Inhibiting diamond graphitization ensures that the high hardness and high wear resistance of diamond powder are fully retained. The fine grains increase the grain boundary area, and the irregular arrangement of atoms at the grain boundary can effectively hinder the movement of dislocations, thereby improving the strength and hardness of the material; on the other hand, the refined grains make the deformation of the material more uniform, reduce stress concentration, and improve the toughness and fatigue resistance of the material. This enables ultra-thin diamond composite materials to better adapt to and maintain good processing performance when facing complex processing conditions (such as intermittent cutting, high-speed cutting, etc.), so that the material can meet the needs of high-speed, high-efficiency and high-precision processing.
[0017] Optionally, yttrium micropowder needs to be added after the diamond micropowder is mixed with the composite binder.
[0018] Optionally, the sintered ultra-thin diamond composite material is placed in a solution containing tungsten carbide and subjected to microwave heating treatment, wherein the microwave frequency of the microwave heating treatment is 2.45 GHz, the power is 1300-1400 W, and the treatment time is 30-60 minutes.
[0019] By adopting the above technical solution, when the solution is heated by microwaves, a strong convection phenomenon will occur. This convection allows the tungsten carbide particles in the solution to fully contact the surface of the extremely thin diamond composite material. Under the high temperature environment of microwave heating, the atomic activity on the surface of the composite material increases, which is conducive to the adsorption and diffusion of tungsten carbide particles on its surface. Within the processing time of 30-60 minutes, tungsten carbide can form a certain diffusion layer on the surface and inside of the material, which will have a strengthening effect on the performance of the material and further improve the hardness and wear resistance of the material.
[0020] Optionally, the surface of the sintered ultra-thin diamond composite material is rinsed with a high-pressure water flow of 380-420 MPa and a spray distance of 25-35 mm for 15-30 minutes.
[0021] By adopting the above technical solution, on the one hand, high-pressure water flow flushing can improve the smoothness of the composite material surface and reduce surface impurities. On the other hand, the continuous shock waves generated by the high-pressure water flow can eliminate the residual stress on the composite material surface without causing damage to the material.
[0022] In summary, this application has the following beneficial effects: 1. Since the present application adopts diamond micropowder and zirconium oxide and polyimide in the composite binder to cooperate with each other, the composite material achieves a good balance of hardness and toughness. It can not only effectively resist wear and impact during processing, but also maintain the shape and performance of the tool when processing various materials, especially difficult-to-process materials, and extend the service life of the tool, helping to obtain higher processing accuracy and surface quality.
[0023] 2. In the present application, yttrium powder is preferably used. Since the surface energy and crystal structure of rare earth element particles are different from those of diamond, diamond atoms are more likely to aggregate and crystallize on their surface, increasing the number of nucleation sites. At the same time, rare earth elements will hinder the diffusion and deposition of atoms to the surface of grains to slow down the growth rate of grains. Under this dual effect, diamond grains are refined, and ultimately a more uniform and fine grain structure is formed.
[0024] 3. The method of the present application, by adopting pulse current sintering compared to the traditional 1500°C high temperature and high pressure sintering, effectively avoids the graphitization transformation of diamond caused by long-term heating at high temperature, and can improve the strength and hardness of diamond, and can better adapt to and maintain good processing performance, so that the material can meet the needs of high-speed, high-efficiency and high-precision processing. DETAILED DESCRIPTION
[0025] The present application is further described in detail below in conjunction with the examples. It is particularly noted that if no specific conditions are specified in the following examples, the experiments are carried out according to conventional conditions or the conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following examples can be obtained from common commercial sources.
[0026] Preparation Example 1 A method for preparing a composite adhesive: Nano-scale zirconium oxide powder is selected, and the particle size range is 40-60nm. The purity of zirconium oxide powder is ≥99%. Diamine and dianhydride are selected as polyimide precursors, and the diamine is 4,4-diaminodiphenyl ether (ODA) and the dianhydride is pyromellitic dianhydride (PMDA). The purity of diamine and dianhydride is ≥99.5%.
[0027] 7 kg of zirconium oxide powder was dispersed in 10 kg of organic solvent N-methylpyrrolidone using an ultrasonic disperser with an ultrasonic power of 300 W and a dispersion time of 30 minutes.
[0028] 30 g of silane coupling agent was added to the dispersed zirconium oxide solution, and the mixture was stirred for reaction at a stirring speed of 400 rpm for 3 hours, thus completing the pretreatment.
[0029] The pretreated zirconium oxide solution was placed in a reaction kettle, and under nitrogen protection, a mixed solution of diamine and dianhydride was added dropwise thereto, the mixed solution containing 1.572 kg of diamine and 1.712 kg of dianhydride, the molar ratio of diamine to dianhydride being 1:1, the reaction temperature was controlled at 180°C, the reaction time was 6 hours, and stirring was required continuously during the reaction at a stirring speed of 200 rpm.
[0030] After the reaction was completed, the reaction product was cooled to room temperature and then centrifuged at a speed of 4000 rpm for 10 minutes.
[0031] The solid product after centrifugation is washed with N-methylpyrrolidone, and then dried in a vacuum drying oven at a drying temperature of 80°C for 12 hours. After drying, the product is crushed to obtain a composite binder with polyimide coated on the surface of zirconium oxide, in which the polyimide accounts for 30% of the total mass.
[0032] Preparation Example 2 A method for preparing a composite adhesive: The method is different from Preparation Example 1 in that 8 kg of zirconium oxide powder, 1.047 kg of diamine and 1.141 kg of dianhydride are used, and the polyimide in the prepared composite adhesive accounts for 20% of the total mass.
[0033] Preparation Example 3 A method for preparing a composite adhesive: The method is different from Preparation Example 1 in that 6 kg of zirconium oxide powder, 2.095 kg of diamine and 2.282 kg of dianhydride are used, and the polyimide in the prepared composite adhesive accounts for 40% of the total mass.
[0034] Preparation Example 4 A method for preparing a composite adhesive: The method is different from Preparation Example 1 in that 9 kg of zirconium oxide powder, 524.63 g of diamine and 571.47 g of dianhydride are used, and the polyimide in the prepared composite adhesive accounts for 10% of the total mass.
[0035] Preparation Example 5 A method for preparing a composite adhesive: The method is different from Preparation Example 1 in that 5 kg of zirconium oxide powder, 2.619 kg of diamine and 2.853 kg of dianhydride are used, and the polyimide in the prepared composite adhesive accounts for 50% of the total mass.
[0036] Example 1 A method for preparing an ultra-thin diamond composite material: Prepare diamond micropowder with a purity of ≥99%, wherein particles with a particle size of 10-100 nm account for 13% of the total mass of the diamond micropowder, and particles with a particle size of 1-10 μm account for 87% of the total mass of the diamond micropowder; the cemented carbide substrate is made of WC-TiC-Co cemented carbide, wherein the WC content of the alloy is 91.5%, the Co content is 7.3%, and the TiC content is 1.2%, the diameter of the cemented carbide substrate is 12 mm, and the thickness is 10 mm; the composite binder is prepared by Preparation Example 1.
[0037] 100 g of diamond powder and 10 g of composite binder were put into a ball mill for mixing, the ball-to-material ratio was controlled at 2:1, the mixing time was 1 h, the rotation speed was 200 rpm, and a mixed powder was obtained.
[0038] Place the cemented carbide substrate into the mold, and then evenly stack the mixed powder on one side of the cemented carbide substrate with a stacking thickness of 2.5 mm. A layered stacking method is adopted, and the thickness of each layer is controlled at 0.5 mm. During the stacking process, a vibrator is used to compact and level the powder.
[0039] Place the mold containing the stacked powder and cemented carbide matrix into the furnace of the pulse current sintering equipment. Apply a pressure of 4.5±0.1GPa to the mold through a pressure device. Under an argon environment, adjust the pulse current density to 250-350A / cm² and the pulse frequency to 5-10Hz through a pulse current control system, so that the sintering temperature is controlled at 800±10℃ and the sintering time is 15 minutes. After the sintering is completed, turn off the equipment, wait for the furnace to cool to room temperature, take out the sintered product, and obtain an ultra-thin diamond composite material.
[0040] Example 2 A method for preparing an ultra-thin diamond composite material: The difference from Example 1 is that 100 g of diamond powder and 8 g of composite binder are put into a ball mill and mixed.
[0041] Example 3 A method for preparing an ultra-thin diamond composite material: The difference from Example 1 is that 100 g of diamond powder and 12 g of composite binder are put into a ball mill and mixed.
[0042] Example 4 A method for preparing an ultra-thin diamond composite material: The difference from Example 1 is that the composite binder is prepared by Preparation Example 2.
[0043] Example 5 A method for preparing an ultra-thin diamond composite material: The difference from Example 1 is that the composite binder is prepared by Preparation Example 3.
[0044] Example 6 A method for preparing an ultra-thin diamond composite material: The difference from Example 1 is that particles with a particle size of 10-100 nm in the micropowder account for 10% of the total mass of the diamond micropowder, and particles with a particle size of 1-10 μm account for 90% of the total mass of the diamond micropowder.
[0045] Example 7 A method for preparing an ultra-thin diamond composite material: The difference from Example 1 is that particles with a particle size of 10-100 nm in the micropowder account for 15% of the total mass of the diamond micropowder, and particles with a particle size of 1-10 μm account for 85% of the total mass of the diamond micropowder.
[0046] Example 8 A method for preparing an ultra-thin diamond composite material: The difference from Example 1 is that a WC-Co cemented carbide substrate is used as the cemented carbide substrate, and the WC content in the alloy is 92.5% and the Co content is 7.5%.
[0047] Example 9 A method for preparing an ultra-thin diamond composite material: The difference from Example 1 is that 100 g of diamond powder, 8 g of composite binder, and 0.3 g of yttrium powder with a particle size of 40-80 nm are put into a ball mill for mixing.
[0048] Example 10 A method for preparing an ultra-thin diamond composite material: The difference from Example 9 is that 100 g of diamond powder, 8 g of composite binder, and 0.2 g of yttrium powder with a particle size of 40-80 nm are placed in a ball mill for mixing.
[0049] Embodiment 11 A method for preparing an ultra-thin diamond composite material: The difference from Example 9 is that 100 g of diamond powder, 8 g of composite binder, and 0.4 g of yttrium powder with a particle size of 40-80 nm are put into a ball mill for mixing.
[0050] Example 12 A method for preparing an ultra-thin diamond composite material: The difference from Example 1 is that the temperature of pulse current sintering is controlled at 700°C.
[0051] Example 13 A method for preparing an ultra-thin diamond composite material: The difference from Example 1 is that the temperature of pulse current sintering is controlled at 900°C.
[0052] Embodiment 14 A method for preparing an ultra-thin diamond composite material: The difference from Example 1 is that the ultra-thin diamond composite material is immersed in an acetone solution containing 25% tungsten carbide and subjected to microwave heating treatment. The microwave frequency of the microwave heating treatment is 2.45 GHz, the power is 1400 W, and the treatment time is 45 minutes. After the treatment is completed, the ultra-thin diamond composite material is removed, washed with water, and then dried.
[0053] Embodiment 15 A method for preparing an ultra-thin diamond composite material: The difference from Example 1 is that the surface of the ultra-thin diamond composite material is rinsed with a high-pressure water flow of 400 MPa and a spray distance of 30 mm for 20 minutes.
[0054] Comparative Example 1 A method for preparing an ultra-thin diamond composite material: The method is different from Example 1 in that no composite binder is added.
[0055] Comparative Example 2 A method for preparing an ultra-thin diamond composite material: The difference from Example 1 is that the composite binder is prepared by Preparation Example 4.
[0056] Comparative Example 3 A method for preparing an ultra-thin diamond composite material: The difference from Example 1 is that the composite binder is prepared by Preparation Example 5.
[0057] 1. Wear resistance test method and conditions: The ultra-thin diamond composite material prepared by the present invention is processed into cylinders of the same size (diameter 10mm, height 5mm), fixed on the tool handle of the CNC lathe, and turned on the granite round bar. The turning parameters are: linear speed 50-200m / min; cutting depth 0.1-0.5mm; feed 0.1-0.5mm / r. After cutting 2000m mileage, the wear degree of the cutting edge is measured under an optical microscope, and the wear ratio is calculated. The wear ratio is the ratio of the volume of the cut material removed to the volume of the tool material worn.
[0058] 2. Impact toughness test method and conditions: The heavy weight impact method is used for testing. The single impact energy is 0.5J. During the test, the sample is placed on the steel plate of the impact frame, and an axial pressure of 1000N is applied to the sample through the steel rod. Then the hammer is dropped several times until the sample is completely destroyed. The number of drops when the sample is destroyed (total impact energy) is used as an indicator to measure the impact resistance of the composite sheet.
[0059] Table 1 Test data Wear ratio Impact toughness / J Example 1 180,000 369 Example 2 170,000 362 Example 3 180,000 367 Example 4 180,000 365 Example 5 180,000 367 Example 6 170,000 361 Example 7 180,000 370 Example 8 180,000 360 Example 9 200,000 378 Example 10 190,000 375 Embodiment 11 200,000 377 Example 12 180,000 370 Example 13 180,000 368 Embodiment 14 190,000 376 Embodiment 15 190,000 372 Comparative Example 1 140,000 320 Comparative Example 2 150,000 353 Comparative Example 3 150,000 365 Combining Example 1 and Comparative Example 1 with Table 1, it can be seen that in Example 1, a composite binder comprising zirconium oxide and polyimide is used to prepare an ultra-thin diamond composite material, and its wear ratio reaches 180,000 and its impact toughness is 369 J. In Comparative Example 1, no composite binder is added, and the wear ratio drops to 140,000 and the impact toughness also drops to 320 J. This shows that the composite binder can significantly improve the wear resistance and impact toughness of the material. The composite binder can effectively bond the diamond powder, making the material more wear-resistant during the cutting process and better able to maintain structural integrity when subjected to impact.
[0060] Combining Examples 1, 4, 5 and Comparative Examples 2-3 and Table 1, it can be seen that after the composite binder in Example 1 is prepared, the polyimide accounts for 30% of the total mass, the wear ratio is 180,000, and the impact toughness is 369J. In Example 4, the composite binder polyimide accounts for 20% of the total mass, and the performance is similar to that of Example 1; in Example 5, the composite binder polyimide accounts for 40% of the total mass, and the performance is also similar to that of Example 1. In Comparative Example 2, the composite binder polyimide accounts for 10% of the total mass, the wear ratio drops to 150,000, and the impact toughness is 353J; in Comparative Example 3, the composite binder polyimide accounts for 50% of the total mass, the wear ratio is 150,000, and the impact toughness is 365J. This shows that the content of polyimide in the composite binder has little effect on the material properties within the scope of this application. When the polyimide content is too high or too low, the wear resistance and impact toughness of the material will decrease.
[0061] It can be seen from Examples 1-3 and Table 1 that the amount of composite binder used has an impact on material properties. The amount added in this application helps to maintain good wear resistance and impact toughness, and an addition amount of 10% is the most preferred in this application.
[0062] Combining Example 1 and Examples 6 and 7 with Table 1, it can be seen that the content of nano-scale particles in the diamond micropowder has an impact on the material properties. Properly increasing the content of nano-scale particles can improve the impact toughness to a certain extent. In this application, the particles with a particle size of 10-100nm in the diamond micropowder account for 13% of the total mass of the diamond micropowder, which is optimal. Balance performance and manufacturing cost, and continue to increase the mass of nano-scale particles will not have much impact on the performance of the composite material.
[0063] Combining Example 1 and Example 8 with Table 1, it can be seen that Example 1 uses a WC-TiC-Co cemented carbide substrate with an impact toughness of 369 J; Example 8 uses a WC-Co cemented carbide substrate with an impact toughness of 360 J. This shows that the composition change of the cemented carbide substrate has little effect on the wear resistance of the material, but has a certain effect on the impact toughness of the material, and the WC-TiC-Co cemented carbide substrate performs better in terms of impact toughness than the WC-Co cemented carbide substrate.
[0064] Combining Example 1 and Examples 9-11 and Table 1, it can be seen that Example 1 does not add yttrium powder, the wear ratio is 180,000, and the impact toughness is 369J; Example 9 adds 0.3g yttrium powder, the wear ratio is increased to 200,000, and the impact toughness is 378J; Example 10 adds 0.2g yttrium powder, the wear ratio is 190,000, and the impact toughness is 375J; Example 11 adds 0.4g yttrium powder, the wear ratio is 200,000, and the impact toughness is 377J. It shows that adding yttrium powder can effectively improve the wear resistance and impact toughness of the material, and can achieve a good effect of strengthening the composite material within the scope of this application.
[0065] Combining Example 1 and Examples 12 and 13 with Table 1, it can be seen that within the sintering temperature range of 700-900°C, the wear resistance of the material is slightly affected, and there is a certain effect on the impact toughness, but the change range is not large. The material can maintain relatively stable performance within this temperature range.
[0066] It can be seen from Example 1 and Examples 14 and 15 and Table 1 that the microwave heating treatment of tungsten carbide solution and the post-treatment process of high-pressure water washing can improve the wear resistance and impact toughness of the material to a certain extent, which helps to improve the comprehensive performance of the material.
[0067] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. An ultra-thin diamond composite material, characterized in that: The invention comprises diamond micropowder, a composite binder and a hard alloy matrix. The composite binder comprises 60-80% of zirconium oxide and 20-40% of polyimide. The amount of the composite binder is 8-12% of the mass of the diamond micropowder.
2. The ultra-thin diamond composite material according to claim 1, characterized in that: The preparation method of the composite binder is: Disperse zirconium oxide powder with a particle size of 40-60 nm in an organic solvent, add a surfactant, and stir to react for 2-4 hours; Under nitrogen protection, a mixed solution of diamine and dianhydride is added to the zirconium oxide dispersion, the molar ratio of diamine to dianhydride is maintained at 1:1, the reaction temperature is controlled at 150-200°C, and the reaction time is 4-8 h; After the reaction is completed, the reaction product is cooled, washed and dried to obtain a composite adhesive.
3. The ultra-thin diamond composite material according to claim 1, characterized in that: In the diamond micropowder, particles with a particle size of 10-100 nm account for 10-15% of the total mass of the diamond micropowder, and particles with a particle size of 1-10 μm account for 85-90% of the total mass of the diamond micropowder.
4. The ultra-thin diamond composite material according to claim 1, characterized in that: It also includes yttrium micropowder with a particle size of 40-80nm, and the added amount of the yttrium micropowder is 0.2-0.4% of the mass of the diamond micropowder.
5. The ultra-thin diamond composite material according to claim 1, characterized in that: The hard alloy substrate is a WC-TiC-Co hard alloy substrate.
6. A method for preparing an ultra-thin diamond composite material according to any one of claims 1 to 5, characterized in that: The following steps are involved: Mix the diamond powder with the composite binder, put the cemented carbide substrate into the mold, and then stack the diamond powder containing the composite binder on one side of the cemented carbide substrate with a stacking thickness of 2-3mm; Pulse current is used to heat and sinter the mold, the pressure is set to 4-5GPa, and the sintering temperature is set to 700-900℃ to obtain an extremely thin diamond composite material.
7. The method for preparing the ultra-thin diamond composite material according to claim 6, characterized in that: After the diamond micropowder is mixed with the composite binder, yttrium micropowder needs to be added.
8. The method for preparing the ultra-thin diamond composite material according to claim 6, characterized in that: The obtained ultra-thin diamond composite material is placed in a solution containing tungsten carbide and subjected to microwave heating treatment, wherein the microwave frequency of the microwave heating treatment is 2.45 GHz, the power is 1300-1400 W, and the treatment time is 30-60 minutes.
9. The method for preparing the ultra-thin diamond composite material according to claim 6, characterized in that: The surface of the obtained ultra-thin diamond composite material is washed with a high-pressure water flow of 380-420 MPa and a spray distance of 25-35 mm for 15-30 minutes.
Citation Information
Patent Citations
Nano-zironia dispersion strengthening diamond composite material and preparation method thereof
CN103146942A
High-temperature and high-pressure cavity assembly structure, polycrystalline diamond composite material and preparation method
CN118404072A
Diamond-containing nanocomposite interfacial layer in fusers
US20100233465A1
Method to generate and disperse nanostructures in a composite material
US20130059074A1
Method and apparatus for forming a gold metal matrix composite
US20140361670A1